Ornithine Decarboxylase Activity in Cultured Endothelial Cells Stimulated by Serum, Thrombin and Serotonin - D’Amore, P A; Hechtman, H B; Shepro, D (Thrombosis and Haemostasis, 1978)
Ornithine decarboxylase (ODC) activity, the rate-limiting step in the synthesis of polyamines, can be demonstrated in cultured, bovine, aortic endothelial cells (EC). Serum, serotonin and thrombin produce a rise in ODC activity. The serotonin-induced ODC activity is significantly blocked by imipramine (10-5 M) or Lilly 11 0140 (10-6M). Preincubation of EC with these blockers together almost completely depresses the 5-HT-stimulated ODC activity. These observations suggest a manner by which platelets may maintain EC structural and metabolic soundness.